Worth more than their weight in gold?. (1st September 2016) - Warren, D.; Buteau, A.; Diven, D.
Summary: The cost of many topical prescription medications has increased in recent years. We have calculated that the cost per unit now exceeds that of many ?valuable' consumer items.